European Law - Koltay, András (Children in Digital Age, 2025)
Abstract:The Internet and digitalization make easier to find information, learn, work, or even entertain, however, it can also give platform to harmful contents and bad practices. The latter two takes many forms, from strong language and unethical marketing strategies to child pornography and bullying. The European Union tries to protect its citizens, especially youth, from cybercrime, and prepare them for the challenges evolving in the online world. This chapter gathers the measures, soft law means and regulations the European Union created to prevent children becoming online victims, and shows not only the related international conventions but the relevant legal cases as well, giving a more complex and comprehensible account of the risks and dangers everybody, especially minors, have to face on the Internet. Keywords: protection of minors, internet regulation, cyberbullying, child pornography, harmful content